Rethinking Obama - Go, Julian, 1970- (Bingley, U.K. : Emerald, 2011)
This volume of "Political Power and Social Theory" includes a selection of papers exploring Obama and the Politics of Race & Religion. Chapters examine the complex dynamics of race relations and racial meaning in America under the Obama administration. The "Scholarly Controversies" section features a debate on Obama and religion in the United States. This volume will be among the first to critically assess the meanings of race and religion in America under the Obama administration, featuring controversial chapters by Phil Gorksi of Yale University and Eduardo Bonilla-Silva of Duke University, among others.
Introduction : examining, debating, and ranting about the Obama phenomenon / Louise Seamster, Eduardo Bonilla-Silva -- The black presidential non-slave : genocide and the present tense of racial slavery / Dylan Rodríguez -- Barack Obama's community organizing as new black politics / Tamara K. Nopper -- The more things change : a Gramscian genealogy of Barack Obama's 'post-racial' politics, 1932-2008 / Cedric de Leon -- The Tea Party in the age of Obama : mainstream conservatism or out-group anxiety? / Matt A. Barreto, Betsy L. Cooper, Benjamin Gonzalez, Christopher S. Parker, Christopher Towler -- The sweet enchantment of color blindness in black face : explaining the 'miracle', debating the politics, and suggesting a way for hope to be 'for real' in America / Eduardo Bonilla-Silva, Louise Seamster -- Barack Obama and civil religion / Philip S. Gorski -- Civil religion and the politics of belonging / Joseph Gerteis -- Civil religion for a diverse polity / Andrew R. Murphy -- The unfinished covenant / Michael P. Young, Christopher Pieper -- Rejoinder : why civil religion? / Philip S. Gorski.
Print version record
Keywords: Obama, Barack; Social Science -- Discrimination & Race Relations; Social Science -- Ethnic Studies -- General; Social Science -- Sociology of Religion; Social groups; Religious groups: social & cultural aspects; Power (Social sciences); Political sociology